2016
DOI: 10.1371/journal.pone.0158716
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Renal Tubular PGC-1α Exacerbates Diet-Induced Renal Steatosis and Age-Related Urinary Sodium Excretion in Mice

Abstract: The kidney has a high energy demand and is dependent on oxidative metabolism for ATP production. Accordingly, the kidney is rich in mitochondria, and mitochondrial dysfunction is a common denominator for several renal diseases. While the mitochondrial master regulator peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) is highly expressed in kidney, its role in renal physiology is so far unclear. Here we show that PGC-1α is a transcriptional regulator of mitochondrial metabolic pathways in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Mitochondrial biogenesis is regulated by a range of transcriptional co-activators and co-repressors 56,57 . One study has shown that PGC1α is a prominent regulator, at the transcriptional level, of oxidative phosphorylation, the TCA cycle and fatty acid metabolism in the kidney 58 . In that study, the investigators performed gene expression profiling of kidneys from control mice and nephron-specific inducible PPARGC1A -knockout (NiPKO) mice that had been fed a chow diet or high-fat diet (HFD).…”
Section: Maintaining Mitochondrial Homeostasismentioning
confidence: 99%
“…Mitochondrial biogenesis is regulated by a range of transcriptional co-activators and co-repressors 56,57 . One study has shown that PGC1α is a prominent regulator, at the transcriptional level, of oxidative phosphorylation, the TCA cycle and fatty acid metabolism in the kidney 58 . In that study, the investigators performed gene expression profiling of kidneys from control mice and nephron-specific inducible PPARGC1A -knockout (NiPKO) mice that had been fed a chow diet or high-fat diet (HFD).…”
Section: Maintaining Mitochondrial Homeostasismentioning
confidence: 99%
“…While these studies strongly indicate a vital role of PGC-1α another group used an inducible nephron specific PGC-1α knockout mouse model to study the physiological role of PGC-1α in the kidney [ 86 ]. Results indicated the role of PGC-1α in mitochondrial metabolic systems is observed in the kidney similar to the previously described roles of PGC-1α in other tissues.…”
Section: Pgc-1α In Kidney Disease and Developmentmentioning
confidence: 99%
“…Results indicated the role of PGC-1α in mitochondrial metabolic systems is observed in the kidney similar to the previously described roles of PGC-1α in other tissues. After inducing the knockout at 12 weeks, researchers noted abnormal sodium excretion, most likely due to the decreased protein expression of sodium transporters NCCT and NKCC2 [ 86 ]. These phenotypes ultimately led to mice presenting with renal steatosis, although the authors hypothesize PGC-1α is dispensable for renal physiology due to mild phenotypes and high survival rates [ 86 ].…”
Section: Pgc-1α In Kidney Disease and Developmentmentioning
confidence: 99%
“…NiPKO mice exhibit a mild loss of sodium in urine, which is exacerbated in aged and HFD‐fed mice, suggesting the beneficial role of tubular PGC‐1α in sodium homeostasis under basal conditions, aging, and metabolic stress. In addition, NiPKO mice develop exacerbated kidney steatosis on a HFD (Svensson, Schnyder, Cardel, & Handschin, ).…”
Section: Role Of Pgc‐1α In Agingmentioning
confidence: 99%